Online Travel Agent Service and Customer Spending Behavior: The influence of Age Generation, User’s location, PayLater Status during COVID 19 Pandemic towards Spending - Kurnia, Candra Harja; Achmadi, Hendra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This necessity of continually improving the service to online customers is an important prerequisite for a better and successful business in all industries, including the Online Travel Agent industry. Mostly during Covid 19 where the travel industry hit the hardest, purchase and booking has emerged as the main objective for OTA to survive. Therefore, understanding the different customer groups in one of the biggest OTA in Indonesia is indispensably crucial. The purpose of this research is to examine whether User's gender, location (cities), and PayLater status have positive correlation on User’s spending, and to eventually help OTA in providing approaches to different customers to increase their sales and bookings especially during the pandemic year.